PENGARUH KUALITAS LAYANAN, KEPERCAYAAN DAN SISA HASIL USAHA TERHADAP KEPUASAN ANGGOTA KOPERASI BANK RAKYAT INDONESIA CABANG MAMUJU - Syarifuddin, Syarifuddin (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2019)
Bank Rakyat Indonesia Cooperative is a business entity consisting of individuals or cooperative legal entities based on its activities based on cooperative principles as well as a people's economic movement based on the principle of kinship. The role of cooperatives as one of the sectors of economic power in Indonesia is expected to realize the people's economic democracy, that is from the people, by the people and for the welfare of the people of Indonesia. In line with the rapid progress of the economy and business in general, the cooperative business grows into increasingly diverse types. This research is a type of quantitative research using multiple linear regression analysis. The results showed that partially or simultaneously variables of service quality, trust and residual business results had a positive and significant effect on member satisfaction.